Misfit modernism queer forms of double exile in the twentieth-century novel - González, Octavio R. (University Park, Pennsylvania : The Pennsylvania State University Press, 2020)
"Revisits the theme of alienation in modernist literature, finding an alternative aesthetic centered on the experience of double exile. Explores examples drawn from the cultural groupings of the New Negro movement, Parisian expatriates in the 1920s, and the queer expatriate scene in Los Angeles before Stonewall"--
Intro -- COVER Front -- Copyright Page -- Table of CONTENTS -- ACKNOWLEDGMENTS -- Introduction -- Notes to Introduction -- Chapter 1: Methodology -- Notes to Chapter 1 -- Chapter 2: Narrating thePsychology of a" Despised Mulatto" in Larsen's Quicksand -- Notes to Chapter 2 -- Chapter 3: Affective Realism -- Notes to Chapter 3 -- Chapter 4: Narrating the Mood of the Underdog in Rhys's Quartet -- Notes to Chapter 4 -- Chapter 5: Isherwood's Impersonality -- Notes to Chapter 5 -- NOTES -- BIBLIOGRAPHY -- INDEX
eBooks on EBSCOhost
Keywords: Alienation (Social psychology) in literature; English fiction -- 20th century -- History and criticism; American fiction -- 20th century -- History and criticism; Modernism (Literature); Queer theory; Aliénation (Psychologie sociale) dans la littérature.; Roman anglais -- 20e siècle -- Histoire et critique; Roman américain -- 20e siècle -- Histoire et critique; Modernisme (Littérature); Théorie queer; LITERARY CRITICISM / Gay & Lesbian; Alienation (Social psychology) in literature; American fiction; English fiction; Modernism (Literature); Queer theory; Modernisme (litterature).; Roman americain -- Auteurs noirs americains -- 20e siecle; Roman anglais -- 20e siecle; Alienation sociale -- Dans la litterature; 1900-1999; Criticism, interpretation, etc